Fine-Needle Aspiration Features of BCOR-CCNB3 Sarcoma: Report of Five Cases. Issue 3 (3rd November 2019) - Gajdzis, Pawel; Laé, Marick; Pierron, Gaëlle; Brisse, Hervé J; Orbach, Daniel; Fréneaux, Paul; Laurence, Valerie; Klijanienko, Jerzy
Abstract: Objectives: BCOR-CCNB3 sarcoma (BCS) is an undifferentiated tumor that has some clinical and morphologic similarity to classic Ewing sarcoma, but it is characterized by a distinct BCOR-CCNB3 gene fusion. There are no reports describing its cytomorphologic findings. Methods: We describe cytologic findings of five molecularly proven BCS cases (four males and one female, aged 8.5-22 years). Results: Smears showed mainly round cells, but some spindle cells and rhabdoid-like cells were also observed. Dispersed cells dominated in smears, but also distinct pseudopapillary structures with vascular cores were noted in four cases. Scant connective tissue fragments were found in four cases. There was no rosette formation in any case. Conclusions: BCS should be differentiated from other round cell tumors. Some cytologic features, especially rhabdoid-like cells, connective tissue fragments, and pseudopapillary formations, combined with immunohistochemical and molecular studies, may be helpful in making the appropriate diagnosis.